KESADARAN HUKUM PEMILIK KENDARAAN PLAT HITAM DALAM MEMANFAATKAN KENDARAAN SEBAGAI ANGKUTAN PENUMPANG - NIM. A1011161290, GEO DESTIAN WICAKSONO (Jurnal Fatwa Hukum, 2023)
ABSTRACTThis thesis is entitled: Legal Awareness of Black Plate Vehicle Owners in Utilizing Vehicles as Passenger Transportation. The formulation of the problem in this thesis research is: "How is the Legal Awareness of Black Plate Vehicle Owners in Utilizing Vehicles as Passenger Transportation". The purpose of the research is to find out and analyze the legal awareness of private car owners in using the vehicle as passenger transportation, to find out and analyze how the legal policy is for private vehicles as passenger transportation and to find out and analyze the government's efforts to overcome the use of private vehicles as passenger transportation. The research method that researchers use is normative legal research method.Based on the results of the study that private car owners do not yet have legal awareness regarding the use of private car vehicles as passenger transportation, because they do not have legal awareness, it is necessary to carry out legal policies by the government as a regulator. This needs to be done so that there is no imbalance between private car owners who use them as passenger transport and official transportation entrepreneurs. Legal policies carried out by the Pontianak city government towards private vehicles as passenger transportation such as making regulations and strict requirements for the operation of private vehicles as public transportation, such as the completeness of vehicle documents, vehicle safety standards, and driver's licenses, making strict and clear rules regarding tariffs that can be applied by drivers of private vehicles operating as public transportation, determining certain areas as operating zones for private vehicles as public transportation, developing applications or platforms that can help the public to access and call private vehicles as public transportation easily and safely, create campaigns for and increase public awareness of the risks associated with using private vehicles as unofficial public transport. The legal remedies taken by the Pontianak City Transportation Agency against private car owners as (public) passenger transport include giving written notification regarding sanctions for vehicle owners, detaining vehicles and ownership documents if they do not have permission and coordinating with the transportation agency (DLLAJR). ) and it is mandatory for violators of the route permit to pay a fine to Bank Kalbar with a stipulation letter from the Pontianak City Transportation Service officer. Keywords: Legal Awareness, Black Plate Vehicle Owners, Passenger Transport   ABSTRAKSkripsi ini berjudul: Kesadaran Hukum Pemilik Kendaraan Plat Hitam Dalam Memanfaatkan Kendaraan Sebagai Angkutan Penumpang. Rumusan masalah dalam penelitian skripsi ini adalah: “Bagaimana Kesadaran Hukum Pemilik Kendaraan Plat Hitam Dalam Memanfaatkan Kendaraan Sebagai Angkutan Penumpang”.Tujuan penelitian adalah untuk mengetahui dan menganalisis mengenai kesadaran hukum pemilik kendaraan mobil pribadi dalam memanfaatkan kendaraan sebagai angkutan penumpang, untuk mengetahui dan menganalisis bagaimana kebijakan hukum terhadap kendaraan pribadi sebagai angkutan penumpang dan untuk mengetahui dan menganalisis upaya pemerintah untuk mengatasi penggunaan kendaraan pribadi sebagai angkutan penumpang.Metode Penelitian yang peneliti gunakan adalah metode penelitian hukum Normatif.Berdasarkan hasil penelitian bahwa pemilik kendaraan mobil pribadi belum memiliki kesadaran hukum tentang penggunaan kendaraan mobil pribadi menjadi angkutan penumpang, oleh karena belum memiliki kesadaran hukum maka perlu dilakukan kebikjakan hukum oleh pemerintah sebagai regulator. Hal tersebut perlu dilakukan agar tidak terjadi ketimpangan antara pemilik kendaraan mobil pribadi yang menjadikannya sebagai angkutan penumpang dan pengusaha transportasi resmi. Upaya hukum yang dilakukan oleh Dinas Perhubungan Kota Pontianak terhadap pemilik kendaraan mobil pribadi sebagai angkutan penumpang (umum) yakni melakukan pemeberitahuan secara tertulis terkait sanksi bagi pemilik kendaraan, menahan kendaraan dan surat-surat kepemilikan apabila tidak memiliki ijin serta melakukan koordinasi dengan dinas perhubungan (DLLAJR) dan diwajibkan bagi pelanggar izin trayek tersebut membayar denda pada Bank Kalbar dengan surat ketentuan dari petugas Dinas Perhubungan kota Pontianak. Kata Kunci : Kesadaran Hukum, Pemilik Kendaraan Plat Hitam, Angkutan Penumpang